Location of recycling bins using covering facility location model in Nilai, Malaysia / Puteri Nur Najihah Mohammad Nizam ... [et al.] - Mohammad Nizam, Puteri Nur Najihah; Zulfika, Zulaikha Nuryn; Hairulanuar, Nurulhusna Najihah; Zaharudin, Zati Aqmar (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2022)
Sustainable waste management systems can be achieved by improving recycling activity among the public. However, public participation is among the biggest challenges (Khamaruddin et al., 2019), as it is initiated through separation at the source activity. To encourage this activity at the household level, it is critical to provide adequate and easily accessible recycling bins in a convenient location. However, establishing these locations is challenging (Woodard et al., 2004), and once implemented, the facility location is difficult to change in the immediate term (Owen & Daskin, 1998). For these reasons, a covering facility location model by Jamiron et al. (2021) is utilized to optimally locate the required facilities with sufficient capacity levels, with an emphasis on optimizing demand coverage.